Hybrid catalyst‐assisted synthesis of multifunctional carbon derived from Camellia shell for high‐performance sodium‐ion batteries and sodium‐ion hybrid capacitors - Hanshu Mao; Sisi Yang; Yingjun Yang; Jinyue Yang; Guizhi Yuan; Mingtao Zheng; Hang Hu; Yeru Liang; Xiaoyuan Yu (Carbon Neutralization, 2024)
Abstract Biomass‐derived carbon as energy storage materials have gradually attracted widespread attention due to their low cost, sustainability, and inherent structural advantages. Herein, hard carbon (H‐1200) and porous carbon (PC‐800) for sodium‐ion batteries (SIBs), sodium‐ion capacitors (SICs) half cells and sodium‐ion hybrid capacitors (SIHCs) have been synthesized from the same biomass precursor of Camellia shells through different treatments. H‐1200 synthesized by directly high‐temperature carbonization possesses a rational graphitic layer structure and plentiful heteroatoms. When applied as anode for SIBs, it exhibits a reversible capacity of 365.5 mAh g–1 at 25 mA g–1 and capacity retention 89.0% after 400 cycles at 200 mA g–1. Additionally, PC‐800 prepared by catalytic carbonization of K2C2O4/CaC2O4 hybrid catalyst has a sophisticated porous structure and a high surface area of 2186.9 m2 g–1. When employed as a cathode for SICs, it delivers a maximum capacity 104.2 mAh g–1 at 100 mA g–1 and 35.0 mAh g–1 at 5 A g–1. Furthermore, the all carbon assembled SIHC (H‐1200||PC‐800) using H‐1200 as anode and PC‐800 as cathode, features a broad output voltage range (0.01 ~ 4.1 V), high energy density of 161.5 Wh kg–1, power density of 12896.1 W kg–1, and superior capacity retention of 90.32% after 10000 cycles at 10 A g–1. This research result provide a new horizon for constructing low‐cost and large‐scale production of biomass derived carbon for energy storage materials.